Parental and student attitudes toward the teaching of ethnic languages in Australia - Smolicz, J. J. (Education quarterly.)
Over the last two years, the University of Adelaide's Department of Education has been studying three different groups of people involved in the education process, parents, teachers, and students and in this case, teacher to be. The studies investigated the extent to which Australian languages other than English were being maintained and studies through questionnaires and interviews. The attitudes toward the preservation and development of Australian languages were also evaluated.